Facial indices of North and South Indian Adults: Reliability in Stature Estimation and Sexual Dimorphism - Prasanna LC; Bhosale S; D’Souza A; Mamatha H; Thomas RH; Sachin KS (Journal of Clinical and Diagnostic Research, 2013)
Introduction: Anthropological studies have document differences in craniofacial features as well as in body characteristics among different populations. The variations in the facial morphology arise through a differential growth and they help us in distinguishing one person from another. These are controlled by a number of factors which include genetic heritage, climate and environment in which we live. Very few researchers from India have worked on these facial features with respect to population and environment. The present work was undertaken to determine whether facial variations were subjected to sexual dimorphism. In addition, comparison of facial indices was made, in order to determine possible variations between south and north Indian populations. Methods: The sample consisted of 200 individuals, 100 each from north and south Indian regions. Various facial parameters were determined on the basis of international anatomical description and facial indices were calculated. Results: North Indian males and females had highest facial height and upper facial height. Facial width of south Indians was more as compared to that of north Indians in both sexes. Regression equation was calculated to compare the probable height with actual height. Conclusion: All the facial parameters and facial indices were found to be statistically highly significant and they showed interregional and gender variations. These indices will be beneficial in facial reconstruction surgeries, maxillofacial surgeries, and in forensic medicine, for estimating the stature and sex of an individual.